Pembentukan Desa Kreatif Rintisan Berbasis Seni Kerajinan Lokal - I Wayan Sudana; Hasdiana Hasdiana; Isnawati Mohamad (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
The formation of creative villages is one of the instruments in improving the economy of rural communities in the creative economy sector. Creative villages can be formed in stages with a certain basis as superior according to the potential of the village. This activity aims to form a pioneering creative village based on local crafts as superior. The implementation of activities using participatory methods and workshops goes through: program socialization, formation of crafter groups, provision of knowledge related to crafts, manufacture of local crafts products, and planning follow-up activities. The results are: 1) increasing public interest in developing local crafts; 2) the formation of a crafter group in the village; 3) increasing community knowledge and skills in making local craft products according to village potential; 4) agreed on a program for continued activities in the development of local crafts in a sustainable manner. The results achieved are an indicator of the formation of a pioneering creative village based on crafts as a superior, which has the opportunity to improve the economy of rural communities in the creative economy sector.